Structural and Phylogenetic Diversity of Anaerobic Carbon-Monoxide Dehydrogenases - Inoue, Masao; Nakamoto, Issei; Omae, Kimiho; Oguro, Tatsuki; Ogata, Hiroyuki; Yoshida, Takashi; Sako, Yoshihiko (Frontiers in Microbiology, 2019)
Anaerobic Ni-containing carbon-monoxide dehydrogenases (Ni-CODHs) catalyze the reversible conversion between carbon monoxide and carbon dioxide as multi-enzyme complexes responsible for carbon fixation and energy conservation in anaerobic microbes. However, few biochemically characterized model enzymes exist, with most Ni-CODHs remaining functionally unknown. Here, we performed phylogenetic and structure-based Ni-CODH classification using an expanded dataset comprised of 1942 non-redundant Ni-CODHs from 1375 Ni-CODH-encoding genomes across 36 phyla. Ni-CODHs were divided into seven clades, including a novel clade. Further classification into 24 structural groups based on sequence analysis combined with structural prediction revealed diverse structural motifs for metal cluster formation and catalysis, including novel structural motifs potentially capable of forming metal clusters or binding metal ions, indicating Ni-CODH diversity and plasticity. Phylogenetic analysis illustrated that the metal clusters responsible for intermolecular electron transfer were drastically altered during evolution. Additionally, we identified novel putative Ni-CODH-associated proteins from genomic contexts other than the Wood–Ljungdahl pathway and energy converting hydrogenase system proteins. Network analysis among the structural groups of Ni-CODHs, their associated proteins and taxonomies revealed previously unrecognized gene clusters for Ni-CODHs, including uncharacterized structural groups with putative metal transporters, oxidoreductases, or transcription factors. These results suggested diversification of Ni-CODH structures adapting to their associated proteins across microbial genomes.